On the light intensity value under photovoltaic arrays for agrivoltaic integration - Ya'acob, Mohammad Effendy; Othman, Noor Fadzlinda; Nazri, Nur Aisha (IEEE, 2022)
The biggest problem in agriculture sector across Malaysia recently, evolve around the limitation of agri-land especially in the urban or sub-urban area where the basic infrastructures have already been in place. Most of agri-land has been converted to industrial land based on increasing demand and faster returns. Agrivoltaic system plays a significant role as a practical solution in mitigating and providing agri space for agricultural activities by means of integration with the existing solar Photovoltaic (PV) farm infrastructure. The area under solar PV array is shaded by the PV modules which is an opaque surface and only receives sunlight thru reflected lights from the ground and openings between modules. The field assessment is conducted in Puchong Solarfarm, Selangor, Malaysia with the generating capacity of 2 MWp using ground-mounted solar structures. Condition under PV arrays can be considered as a low light intensity but unfortunately the estimated value of light penetration for the agri-space have not been discussed in literature. Thus, this study provides some field information on the light intensity value for spot location directly underneath solar PV in comparison with direct sunlight spot area. This information would assist solar operators and potential farmers to established suitable crops in the solarfarm infrastructures as means of optimizing the solarfarm area.